Method for converting waste lead plaster into lead-carbon composite material in short process

The waste lead paste is converted into lead-carbon composite materials through short-process methods, which solves the problems of long process flow and large reagent consumption in the hydrometallurgy process, realizes efficient lead recovery and electrode material preparation, and improves resource utilization efficiency and battery performance.

CN119297455APending Publication Date: 2025-01-10GUANGDONG INST OF ECO ENVIRONMENT & SOIL SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411294332.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The recycling process of waste lead paste in the existing wet metallurgy process is long and the reagents are consumed, resulting in waste of resources and environmental pollution. The lead-acid battery has problems such as positive electrode expansion and negative electrode irreversible sulfurization, which affects battery performance.

Method used

The short process method is adopted to mix waste lead paste with leaching agent and process it with anion exchange resin to remove sulfate ions, and prepare lead-carbon composite materials through crystallization and pyrolysis, simplifying the process flow and improving the recovery efficiency of lead.

Benefits of technology

It realizes efficient recycling of waste lead paste and preparation of lead-carbon composite materials, shortens the process flow, reduces reagent consumption, improves the leachate rate of lead and the performance of electrode materials, and improves resource utilization efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297455A_ABST
    Figure CN119297455A_ABST
Patent Text Reader

Abstract

The invention discloses a method for converting waste lead plaster into a lead-carbon composite material in a short process, and relates to the technical field of solid waste utilization. The method comprises the following steps: mixing the waste lead plaster with a leaching agent, leaching, and carrying out solid-liquid separation to obtain a lead plaster leaching solution; mixing the lead plaster leachate with anion exchange resin, adsorbing and removing sulfate ions, and carrying out solid-liquid separation to obtain a purified solution; performing crystallization treatment on the purified liquid to obtain a precursor; and pyrolyzing the precursor to obtain the lead-carbon composite material. According to the method, desulfurization conversion and lead leaching in the lead plaster are achieved in one step, use of a desulfurization reagent in an existing hydrometallurgy process is avoided, upgrading utilization of conversion of the lead plaster into the lead-carbon composite material is achieved in a short-process mode, the technological process is shortened, the method has the advantages of being low in energy consumption, simple, efficient and the like, and the method is suitable for industrial production. And a new way which is low in cost and easy to industrialize is provided for recycling, upgrading and utilizing the waste lead plaster.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste utilization, and in particular to a method for converting waste lead paste into a lead-carbon composite material in a short process. Background Art

[0002] The continuous development of industries such as electric vehicles and wind power storage has promoted the steady growth of the use of lead-acid batteries. Statistics show that about 40% to 60% of lead concentrates are used in the production and application of lead-acid batteries, which will inevitably lead to a continuous increase in the output of waste lead-acid batteries. Improper disposal of waste lead-acid batteries poses a major environmental threat and is also a waste of resources, so it is necessary to achieve the recovery and utilization of lead in waste lead-acid batteries. The main lead-containing waste in waste lead-acid batteries is waste lead paste. The waste lead paste has complex components and high impurity content. Its regeneration and disposal is the most critical part of the recycling of waste lead-acid batteries. At present, the disposal methods of waste lead paste mainly include pyrometallurgical and hydrometallurgical processes. Among them, hydrometallurgy is widely used due to its mild reaction conditions, low energy consumption and low pollution.

[0003] Conventional hydrometallurgical processes are generally "desulfurization conversion-reduction leaching-precipitation-roasting", and lead oxide powder can be obtained after this process. For example, a method for recovering lead from waste lead-acid battery lead paste disclosed in the prior art uses ammonium carbonate as a desulfurizer, desulfurizes the lead sulfate in the lead paste, and then uses nitric acid, acetic acid and hydrogen peroxide for acid leaching and reduction leaching. The obtained lead-containing leachate is recovered by precipitation and electrolysis. Another example is a method for recovering high-purity lead oxide from waste lead paste of lead-acid batteries disclosed in the prior art, which uses alkali to convert the lead sulfate in the lead paste into lead oxide, and then uses acetic acid to reduce the lead oxide and lead in the desulfurized lead paste, and the lead dioxide is dissolved with acetic acid, and finally all the lead-containing waste in the lead paste is converted into lead acetate, which is filtered, separated and impurities are removed, and the lead acetate filtrate is precipitated and roasted to prepare lead oxide and byproduct sodium acetate, thereby realizing the recycling of waste lead paste. However, these methods usually require the use of multiple types of solvents such as desulfurization reagents, leaching agents, and precipitants, and have process problems such as large reagent consumption and long process flow.

[0004] At the same time, commercial lead-acid batteries are facing problems such as positive electrode expansion and irreversible sulfation of the negative electrode, which greatly inhibit the capacity and performance of lead-acid batteries. Changing the lead negative electrode of lead-acid batteries into a lead / carbon composite material can effectively alleviate these shortcomings. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a method for converting waste lead paste into a lead-carbon composite material in a short process, so as to realize the recycling of waste lead paste and provide a lead-carbon composite material that can be used for lead-acid battery electrodes.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides a method for converting waste lead paste into a lead-carbon composite material in a short process, comprising the following steps:

[0008] Mixing the waste lead paste with a leaching agent, leaching, and separating the solid from the liquid to obtain a lead paste leachate;

[0009] The lead paste leachate is mixed with an anion exchange resin to remove sulfate ions by adsorption, and solid-liquid separation is performed to obtain a purified solution;

[0010] The purified liquid is subjected to crystallization treatment to obtain a precursor; the precursor is pyrolyzed to obtain a lead-carbon composite material.

[0011] The present invention utilizes a leaching agent to leach lead-containing components, such as lead sulfate, lead dioxide, lead monoxide and single lead, from waste lead paste, and then utilizes an anion exchange resin to adsorb and remove sulfate anions from the leachate, and the lead salt obtained after solution crystallization can be pyrolyzed to prepare a lead-carbon composite material. The lead-carbon composite material can be used as a battery electrode material, and a lead-carbon composite electrode material can be prepared while realizing the recycling of waste lead paste. The method of the present invention is a hydrometallurgical process with the advantages of short process flow and high efficiency. By converting waste lead paste of lead-acid batteries into lead-carbon composite materials, the problems of long process flow and large reagent consumption in the existing hydrometallurgical process are effectively solved.

[0012] Among them, "short process" refers to a short process flow.

[0013] In some embodiments of the present invention, the leaching temperature is 10-100°C.

[0014] In some preferred embodiments of the present invention, the leaching temperature is 20-40°C.

[0015] In some specific embodiments of the present invention, the leaching temperature is 20-30°C.

[0016] In some embodiments of the present invention, the leaching time is 10 to 360 minutes.

[0017] In some preferred embodiments of the present invention, the leaching time is 1 to 3 hours.

[0018] In some specific embodiments of the present invention, the leaching time is 1.5 to 2.5 hours.

[0019] In some embodiments of the present invention, the liquid-to-solid ratio of the leaching agent to the waste lead paste is (10-200) mL: 1 g.

[0020] In some preferred embodiments of the present invention, the liquid-to-solid ratio of the leaching agent to the waste lead paste is (90-100) mL: 1 g.

[0021] In some embodiments of the present invention, the leaching agent includes peracetic acid solution and acetate solution; and / or, the acetate includes at least one of sodium acetate, potassium acetate, and ammonium acetate.

[0022] In some embodiments of the present invention, the volume concentration of the peracetic acid solution is 0.1-15%; the concentration of the acetate solution is 0.5-5 mol / L.

[0023] In some preferred embodiments of the present invention, the volume concentration of the peracetic acid solution is 0.5-3%; the concentration of the acetate solution is 0.5-3 mol / L.

[0024] In some specific embodiments of the present invention, the volume concentration of the peracetic acid solution is 0.5-3%; the concentration of the acetate solution is 2-3 mol / L.

[0025] The volume concentration of the peracetic acid solution here is the volume concentration in the sodium acetate solution.

[0026] In some embodiments of the present invention, the pH during the adsorption process is 2-6.

[0027] In some preferred embodiments of the present invention, the pH during the adsorption process is 2-4.

[0028] In some specific embodiments of the present invention, the pH during the adsorption process is 2-3.

[0029] Specifically, the pH during the adsorption process is adjusted by adjusting the pH of the leachate.

[0030] In some embodiments of the present invention, the adsorption temperature is 10-90°C.

[0031] In some embodiments of the present invention, the adsorption time is 10 min to 12 h.

[0032] In some preferred embodiments of the present invention, the adsorption time is 1 to 3 hours.

[0033] In some embodiments of the present invention, the anion exchange resin is added in an amount of 10 to 100 g / L relative to the leachate.

[0034] In some preferred embodiments of the present invention, the anion exchange resin is added in an amount of 40 to 50 g / L relative to the leachate.

[0035] In some specific embodiments of the present invention, the amount of anion exchange resin added to the leaching solution is 45-50 g / L.

[0036] In some embodiments of the present invention, the waste lead paste comes from discarded lead-acid batteries; the waste lead paste includes lead sulfate, lead dioxide, lead monoxide and single lead.

[0037] In some preferred embodiments of the present invention, the waste lead paste comprises, by mass fraction, 50-55% lead sulfate, 30-40% lead dioxide, 7-9% lead monoxide and 2-3% single lead.

[0038] In some specific embodiments of the present invention, the waste lead paste comprises, by mass fraction, 52-53% lead sulfate, 35-36% lead dioxide, 8-9% lead monoxide and 2-3% single lead.

[0039] In some embodiments of the present invention, the anion exchange resin is at least one of D201 strong basic anion exchange resin, IRA-400 strong basic anion exchange resin, D311 weak basic anion exchange resin, and IRA-900 weak basic anion exchange resin.

[0040] In some embodiments of the present invention, the pyrolysis temperature is 400-800°C.

[0041] In some preferred embodiments of the present invention, the pyrolysis temperature is 400-600°C.

[0042] In some specific embodiments of the present invention, the pyrolysis temperature is 400-500°C.

[0043] In some embodiments of the present invention, the pyrolysis time is 0.5 to 6 hours.

[0044] In some preferred embodiments of the present invention, the pyrolysis time is 0.5 to 3 hours.

[0045] In some specific embodiments of the present invention, the pyrolysis time is 1 to 2 hours.

[0046] In some embodiments of the present invention, the pyrolysis is performed under an inert atmosphere.

[0047] In some preferred embodiments of the present invention, the inert atmosphere is nitrogen or argon.

[0048] In some embodiments of the present invention, the crystallization method is evaporative crystallization.

[0049] In some preferred embodiments of the present invention, the temperature of the evaporation crystallization is 80-100°C.

[0050] In some preferred embodiments of the present invention, the evaporation crystallization time is 1 to 24 hours.

[0051] Specifically, the basic principle of the present invention is as follows: peracetic acid undergoes an oxidation-reduction reaction with lead dioxide in waste lead paste to convert it into lead monoxide, and then lead sulfate, lead monoxide and lead are leached out under the action of acetic acid and sodium acetate (Formulas (1) to (5)), and an anion exchange resin is used to adsorb and remove sulfate anions from the leaching solution, and the lead acetate obtained after the solution crystallizes is thermally decomposed to prepare a lead-carbon composite material (Formula (6)). The specific reaction process is as follows:

[0052] 2PbO2 + 4CH3COOOH = 2Pb(CH3COO)2 + 3O2 + 2H2O (1)

[0053] CH3COOOH + PbO2 = PbO + CH3COOH (2)

[0054] Pb + CH3COOOH = PbO + CH3COOH (3)

[0055] PbO + 2CH3COOH = Pb(CH3COO)2 + H2O (4)

[0056] PbSO4 + 2CH3COONa = Pb(CH3COO)2 + Na2SO4 (5)

[0057] Pb(CH3COO)2 = Pb + 3C + 3H2O + CO (6)

[0058] The second aspect of the present invention provides a lead-carbon composite material prepared by the preparation method described in the first aspect of the present invention.

[0059] Compared with the prior art, the present invention has the following beneficial effects:

[0060] The method for preparing a lead-carbon composite material for an electrode from waste lead paste of the present invention can realize the desulfurization conversion of lead sulfate in the waste lead paste and the leaching of lead in one step, thus avoiding the use of a large amount of desulfurization reagents and multiple types of leaching reagents and shortening the process flow.

[0061] Meanwhile, the method of the present invention is simple and efficient in the recovery process of lead in waste lead paste, the lead leaching rate is above 99%, and the resin adsorbing sulfate ions can be recycled.

[0062] The method of the present invention converts waste lead paste into a lead-carbon composite electrode material having a higher capacity than a lead negative electrode, upgrades the utilization mode of the waste lead paste, and improves the resource utilization efficiency of the waste lead paste. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 The process flow chart of an embodiment of the present invention.

[0064] Figure 2 is a comparison chart of leaching rates under different leaching conditions in Examples 1 and 5 to 8 of the present invention; wherein, Figure 2 a is the leaching rate under the conditions of adding one of peracetic acid and sodium acetate alone or a mixture of the two; Figure 2 b is the effect of different sodium acetate solution concentrations on lead leaching in lead paste; Figure 2 c is the effect of different peracetic acid volume concentrations on lead leaching in lead paste.

[0065] Figure 3 This is a comparison chart of the adsorption removal rate of sulfate ions under different pH conditions in Example 9 of the present invention.

[0066] Figure 4 1 is the XRD diagram of the lead-carbon composite material at different pyrolysis temperatures in Example 10 of the present invention. DETAILED DESCRIPTION

[0067] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0068] The waste lead paste used in the following embodiments of the present invention comes from waste lead-acid batteries, and its components include PbSO4: 52.62%; PbO2: 35.48%; PbO: 8.05%; Pb: 3.56%; and others: 0.29%.

[0069] In the following embodiments of the present invention, the lead leaching rate is calculated as follows (7):

[0070] Lead leaching rate (%) = (lead concentration in leachate × leachate volume × 100) / (lead content in solid) (7);

[0071] The removal rate of sulfate ions is calculated as follows (8):

[0072] The removal rate of sulfate ions (%) = (sulfate ion concentration in the initial solution - sulfate ion concentration in the solution after adsorption) × 100 / sulfate ion concentration in the initial solution (8).

[0073] The process flow of the embodiment of the present invention is as follows Figure 1 The following is a detailed description in conjunction with specific embodiments.

[0074] Example 1

[0075] This embodiment provides a method for converting waste lead paste into a lead-carbon composite material in a short process, comprising the following steps:

[0076] Prepare 20 mL of 2.5 mol / L sodium acetate solution, add 0.2 g of lead paste, and then add 1 mL of peracetic acid with a volume concentration of 15% for stirring and leaching. The leaching temperature is 25° C. and the leaching time is 2 h to obtain a lead leaching solution;

[0077] The calculated lead leaching rate is 99.57%. Figure 2 As shown in b;

[0078] The pH of the leaching solution was adjusted to 2, and 1.0 g of D201 type strong alkaline anion resin was added to remove sulfate anions. The adsorption temperature was 25° C. After adsorption for 2 hours, the removal rate of sulfate ions was calculated to be 100%, and a purified solution was obtained;

[0079] The purified liquid was evaporated and crystallized at 90 °C for 12 h to obtain a precursor, which was then pyrolyzed at 400 °C for 1 h in a nitrogen atmosphere to obtain a lead-carbon composite material. Figure 4 shown.

[0080] Example 2

[0081] This embodiment provides a method for converting waste lead paste into a lead-carbon composite material in a short process, comprising the following steps:

[0082] Prepare 20 mL of 2.5 mol / L sodium acetate solution, add 0.2 g of lead paste, and then add 1 mL of peracetic acid with a volume concentration of 15% to react by stirring. The leaching temperature is 25° C. and the leaching time is 2 h to obtain a lead leaching solution;

[0083] The calculated lead leaching rate is 99.57%. Figure 2 As shown in b;

[0084] The pH of the leaching solution was adjusted to 2, and 1.0 g of D201 type strong alkaline anion resin was added to remove sulfate anions. After adsorption for 2 hours, the removal rate of sulfate ions was 100%, and a purified solution was obtained;

[0085] The purified liquid was evaporated and crystallized at 90°C to obtain a precursor. After pyrolysis at 205°C for 1h in a nitrogen atmosphere, a certain amount of lead acetate was obtained in the lead-carbon composite material. The results are as follows Figure 4 shown.

[0086] Example 3

[0087] This embodiment provides a method for preparing a lead-carbon composite material, comprising the following steps:

[0088] Prepare 20 mL of 0.5 mol / L sodium acetate solution, add 0.2 g of lead paste, and then add 1 mL of 15% peracetic acid by volume for stirring reaction. The leaching temperature is 25° C. and the leaching time is 2 h to obtain a lead leaching solution;

[0089] The calculated lead leaching rate is 72.69%. Figure 2 As shown in b;

[0090] The pH of the lead leaching solution was adjusted to 2, and 1.0 g of D201 type strong alkaline anion resin was added to remove sulfate anions. After adsorption for 2 hours, the removal rate of sulfate ions was 100%, and a purified solution was obtained;

[0091] The purified liquid was evaporated and crystallized at 100°C to obtain a precursor, which was then pyrolyzed at 400°C for 1 h in a nitrogen atmosphere to obtain a lead-carbon composite material.

[0092] Example 4

[0093] This embodiment provides a method for converting waste lead paste into a lead-carbon composite material in a short process, comprising the following steps:

[0094] Prepare 20 mL of 2.5 mol / L sodium acetate solution, add 0.2 g of lead paste, and then add 1 mL of 15% peracetic acid by volume for stirring reaction. The leaching temperature is 25° C. and the leaching time is 2 h to obtain a lead leaching solution.

[0095] The calculated lead leaching rate is 99.57%. Figure 2 As shown in b;

[0096] The pH of the leaching solution was adjusted to 6, and 1.0 g of D201 strong alkaline anion resin was added to remove sulfate anions. After 2 h of adsorption, the removal rate of sulfate ions was 35.29%. Figure 3 As shown, after three times of adsorption, the removal rate of sulfate radicals reached 100%, and a purified liquid was obtained;

[0097] The purified liquid was evaporated and crystallized at 100°C to obtain a precursor, which was then pyrolyzed at 400°C for 1 h in a nitrogen atmosphere to obtain a lead-carbon composite material.

[0098] Embodiment 5-6

[0099] This embodiment provides a method for converting waste lead paste into a lead-carbon composite material in a short process. The difference from Embodiment 1 is that: Embodiment 5 only adds sodium acetate solution as a leaching agent; Embodiment 6 only adds peracetic acid solution as a leaching agent.

[0100] Example 7

[0101] The present embodiment provides a method for converting waste lead paste into a lead-carbon composite material in a short process. The difference from Example 1 is that different concentrations of sodium acetate solution are set, and the concentrations of sodium acetate solution are 0.25 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, and 3 mol / L, respectively, to explore the effects of different concentrations of sodium acetate solution.

[0102] Example 8

[0103] This embodiment provides a method for converting waste lead paste into a lead-carbon composite material in a short process. The difference from Example 1 is that different peracetic acid concentrations are set, and the volume concentrations of peracetic acid in sodium acetate solution are 0, 0.25%, 0.5%, 0.75%, 1.5%, and 3%, respectively, to explore the effects of different peracetic acid concentrations.

[0104] Example 9

[0105] This embodiment provides a method for converting waste lead paste into a lead-carbon composite material in a short process. The difference from Example 1 is that different pH conditions are set, and the pH values ​​are 2, 4, 6, 8, and 10, respectively, to explore the effects of different pH values.

[0106] Example 10

[0107] This embodiment provides a method for converting waste lead paste into lead-carbon composite material in a short process. The difference from Example 1 is that different pyrolysis temperatures are set, and the pyrolysis temperatures are 205°C, 265°C, 320°C, 370°C, and 400°C, respectively, to explore the influence of different pyrolysis temperatures.

[0108] Figure 2 This is a comparison chart of the leaching rates under different leaching conditions in Examples 1 and 5 to 8 of the present invention. Figure 2 a is the leaching rate under the conditions of adding one of peracetic acid (PAA) and sodium acetate (NaAc) alone and the mixed reagent (PAA+NaAc), the leaching temperature is 25°C, and the leaching time is 2h; Figure 2 b is the effect of different sodium acetate solution concentrations on the leaching of lead in lead paste, the leaching temperature is 25°C, the leaching time is 2h, and the amount of peracetic acid added is 3%; Figure 2 c is the effect of different volume concentrations of peracetic acid on the leaching of lead in lead paste, the leaching temperature is 25°C, the leaching time is 2h, and the concentration of sodium acetate is 2.5mol / L. Figure 2It can be seen from a that the leaching effect of using a mixed reagent of peracetic acid and sodium acetate in Example 1 is better than that of using peracetic acid alone in Example 6 or using sodium acetate alone in Example 5; Figure 2 In b, the concentration of sodium acetate solution has a significant effect on the leaching rate of lead in waste lead paste, and the leaching effect is best when the concentration reaches 2.5 mol / L; Figure 2 In c, the concentration of peracetic acid solution (PAA) also affects the lead leaching rate, but when the concentration of peracetic acid solution exceeds 0.5%, the leaching rate remains basically unchanged.

[0109] Figure 3 This is a comparison chart of the adsorption removal rate of sulfate ions under different pH conditions in Example 9 of the present invention. It can be seen that different pH values ​​of the leaching solution have a greater impact on the subsequent adsorption and removal of sulfate ions, and a pH value of 2 to 4 is preferably used.

[0110] Figure 4 1 is the XRD diagram of the lead-carbon composite material at different pyrolysis temperatures in Example 10 of the present invention.

[0111] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for converting waste lead paste into lead-carbon composite material in a short process, characterized in that: The steps include: Mixing the waste lead paste with a leaching agent, leaching, and separating the solid from the liquid to obtain a lead paste leachate; The lead paste leachate is mixed with an anion exchange resin to remove sulfate ions by adsorption, and solid-liquid separation is performed to obtain a purified solution; The purified liquid is subjected to crystallization treatment to obtain a precursor; the precursor is pyrolyzed to obtain a lead-carbon composite material.

2. The method according to claim 1, characterized in that The leaching temperature is 10-100° C.; and / or, the leaching time is 10-360 min; and / or, the liquid-to-solid ratio of the leaching agent to the waste lead paste is (10-200) mL:1 g.

3. The method according to claim 1 or 2, characterized in that: The leaching agent includes peracetic acid solution and acetate solution; and / or, the acetate includes at least one of sodium acetate, potassium acetate and ammonium acetate.

4. The method according to claim 3, characterized in that The volume concentration of the peracetic acid solution is 0.1-15%; the concentration of the acetate solution is 0.5-5 mol / L.

5. The method according to claim 1, characterized in that The pH value during the adsorption process is 2 to 6; and / or the adsorption temperature is 10 to 90° C.; and / or the adsorption time is 10 min to 12 h; and / or the amount of the anion exchange resin added to the leaching solution is 10 to 200 g / L.

6. The method according to claim 1, characterized in that The waste lead paste comes from discarded lead-acid batteries; the waste lead paste includes lead sulfate, lead dioxide, lead monoxide and single lead.

7. The method according to claim 1 or 5, characterized in that: The anion exchange resin is at least one of D201 strong basic anion exchange resin, IRA-400 strong basic anion exchange resin, D311 weak basic anion exchange resin, and IRA-900 weak basic anion exchange resin.

8. The method according to claim 1, characterized in that The crystallization method is evaporative crystallization; And / or, the temperature of the evaporation crystallization is 80-100°C.

9. The method according to claim 1, characterized in that: The pyrolysis temperature is 400-800° C.; and / or, the pyrolysis time is 0.5-6 hours; and / or, the pyrolysis is performed under an inert atmosphere.

10. The lead-carbon composite material prepared by the method according to any one of claims 1 to 9.